Refugee Routes Telling, Looking, Protesting, Redressing - Agnew, Vanessa; Konuk, Kader; Newman, Jane O. (The Academy in Exile Book Series, 2020)
The displaced are often rendered silent and invisible as they journey in search of refuge. Drawing on historical and contemporary examples from Turkey, the Ottoman Empire, Iraq, Syria, UK, Germany, France, the Balkan Peninsula, US, Canada, Australia, and Kenya, the contributions to this volume draw attention to refugees, asylum seekers, exiles, and forced migrants as individual subjects with memories, hopes, needs, rights, and a prospective place in collective memory. The book's wide-ranging theoretical, literary, artistic, and autobiographical contributions appeal to scholarly and lay readers who share concerns about the fate of the displaced in relation to the emplaced in this age of mass mobility.